Standardized Slow Enteral Feeding Protocol and the Incidence of Necrotizing Enterocolitis in Extremely Low Birth Weight Infants. (14th October 2014) - Viswanathan, Sreekanth; McNelis, Kera; Super, Dennis; Einstadter, Douglas; Groh‐Wargo, Sharon; Collin, Marc
Abstract : Background: Compared with early enteral feeds, the delayed introduction and slow advancement of enteral feedings to reduce the incidence of necrotizing enterocolitis (NEC) are not well studied in extremely low birth weight (ELBW) infants. Objective : To study the effects of a standardized slow enteral feeding (SSEF) protocol in ELBW infants. Methods : ELBW infants who followed an SSEF protocol (September 2009 to December 2012) were compared with a similar group of historical controls (January 2003 to July 2009). Short‐term outcomes between the 2 groups were compared by propensity score (PS) analysis. Results : One hundred twenty‐five infants in the SSEF group were compared with 294 historical controls. Compared with the controls, feeding initiation day, full enteral feeding day, parenteral nutrition (PN) days, and total central line days were longer in the SSEF group. There was no significant difference in overall NEC (5.6% vs 11.2%, respectively; P = .10) or surgical NEC (1.6% vs 4.8%, respectively; P = .17) between the SSEF group and controls. However, in infants with birth weight <750 g, NEC (2.1% vs 16.2%, respectively; P < .01) or combined NEC/death (12.8% vs 29.5%, respectively; P = .03) was significantly less in the SSEF group compared with controls. In infants who survived to discharge, there was no significant difference in the discharge weight or length of stay in PS‐adjusted analysis. Conclusions : An SSEF protocol significantly reduces the incidence of NEC and combined NEC/death in infants with birth weight <750 g. Despite taking longer to achieve full enteral feeding on this protocol, surviving ELBW infants demonstrated comparable weight gain at discharge without prolonging their hospital stay.